2016
DOI: 10.2136/sssaj2015.05.0202
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical Transformations and Soil Development in Shale across a Latitudinal Climosequence

Abstract: PedologyTo investigate factors controlling soil formation, we established a climosequence as part of the Susquehanna-Shale Hills Critical Zone Observatory (SSHCZO) in central Pennsylvania, USA. Sites were located on organic matter-poor, iron-rich Silurian-aged shale in Wales, Pennsylvania, Virginia, Tennessee, Alabama, and Puerto Rico, although this last site is underlain by a younger shale. Across the climosequence, mean annual temperature (MAT) increases from 7 to 24°C and mean annual precipitation (MAP) ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 69 publications
1
3
0
1
Order By: Relevance
“…On the other hand, the uniform distribution of kaolinite in the investigated soil horizons indicated that kaolinite might be crystallized from percolating soil solutions, rich in Al and Si, similarly to cases described in other studies (Dere et al 2016;Dixon 1989;Skiba 2007). It is worth noting that in the studied soils, kaolinite appeared to be formed both in acidic and alkaline conditions.…”
Section: The Origin Of Identified Clay Minerals In Studied Soilssupporting
confidence: 83%
“…On the other hand, the uniform distribution of kaolinite in the investigated soil horizons indicated that kaolinite might be crystallized from percolating soil solutions, rich in Al and Si, similarly to cases described in other studies (Dere et al 2016;Dixon 1989;Skiba 2007). It is worth noting that in the studied soils, kaolinite appeared to be formed both in acidic and alkaline conditions.…”
Section: The Origin Of Identified Clay Minerals In Studied Soilssupporting
confidence: 83%
“…Geophytes are generally absent from such places, while hemicryptophytes and chamaephytes (plants with buds on persistent aboveground shoots, near the soil surface) dominate (Dahl, 1975; Klimešová et al., 2012). Low temperature and biomass production also slow soil development, thus there is less soil available for the protection and growth of belowground structures (Dere et al., 2016).…”
Section: The Perennating Organs Of Herbs In An Ecological Contextmentioning
confidence: 99%
“…Andesin merupakan kelompok plagioklas-feldspar dengan 50-70% albit dan 30-50% anorthit (Schumann, 1991). Mineral andesin umumnya menghasilkan liat illit dan sedikit kaolinit (Dere et al, 2016).…”
Section: Mineralogi Pasirunclassified